EXPERIENCE REPORT OF AN OPERATION OF THE EXTENSIONIST NUCLEUS RONDON (NER-UDESC): NOTES ON THE APPLICATION OF A WORKSHOP ON THEMATIC SEXUALITY (Citizenship in Action: Extension and Culture Magazine, 2023)
The indissociability between teaching, research and extension is understood in what concerns the support and formation of the university institution, as the stage of technical and professional development of the community that represents, acts and is formed in this space. And having the knowledge that the interventional and training practices in these spaces have variation, it is pertinent to invest in the approximation between scientific, popular and, mainly, humanized knowledge, which is reinforced by the extension actions. In this way, the present work aims to present the results obtained from the application of a workshop developed and applied with the sexuality theme during an Operation of the Extension Center Rondon of the University of the State of Santa Catarina (NER-UDESC) entitled Operation Elpídio Barbosa, which took place in the city of Joinville in 2015. Human sexuality, the theme of this workshop, is represented by a diversity of aspects, perspectives and expressions, however, for the development of the workshop in question, it was decided to focus on three essential points: gender identity, sexual orientation and biological sex. The workshop was carried out with three groups of students, aged 13 to 16, and lasted 90 minutes each, adding a total of 50 participants. The workshop was based on the presentation of a doll and a doll, drawn on a sheet and represented by three points: 1 - the head (space of ideas); 2 - the trunk (space of emotions); 3 - genitalia / chromosomes (gender and sexual interest); and in motivating the participants to present and share their impressions on each of the points. The results presented and discussed in this work were collected from these speeches, speeches and notes made by the participants, of which we can highlight: the debate about the provision of a unisex bathroom in empathy with homosexual and transgender colleagues and minimizing the characterization by biological sex; the differences in treatments in the school and family environment demarcated by the gender of the student; and the reflections guided by the way that social relations are constituted, in the weakened perception about the discourses verbalized by the young people, and the urgency of their political legitimation. Finally, we conclude with the present work that the university extension allows the dialogues between theory and practice to go beyond the academic environment, and to get involved with the general community, and that the Operations and Actions of the NER-UDESC has promoted meetings, debates and activities based on the logic of knowledge sharing and approximation between the academic environment and the community. Having said that, we hope that this work will contribute to a greater appreciation of university extension, as well as increasing the interest of students, teachers and technicians in participating in these actions.
Keywords: University Extension; Rondon Extension Center (NER); Sexuality; Gender